Pendidikan Magang Keterampilan Pangkas Rambut di Kota Tomohon - Djony M. Saroinsong; Mozes M. Wullur; Doni Doni (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research problem is formulated as follows: How is the planning for barbering skills apprenticeship education in Tomohon City. What is the process for barbering skills apprenticeship education in Tomohon city. What are the results of the Hairdressing Apprenticeship Education in the city of Tomohon. What are the results of the Hairdressing Apprenticeship Education in the city of Tomohon. The aim of this research is to describe the implementation of Barbering Apprenticeship Education in Tomohon City. Then what is the process of hairdressing apprenticeship training in Tomohon City and to find out the results of the hairdressing apprenticeship service in Tomohon City. To realize this goal, the researcher used qualitative methods. The informants in this research were 3 people, namely the owner of Barberhood, the owner of Pangkas Rambut Madura and the study residents. Data was collected using techniques: (1) Interview, (2) Observation, (3) Documentation Study. Data were analyzed using the Miles and Huberman Model (in Sugiono 2012: 247), namely (1) Data Collection, (2) Data Reduction, (3) Data Presentation, (4) Verification. From the results of this research, it can be concluded that the plan for the Barbering skills apprenticeship education program for apprentices at Baberhood in Tomohon City has been made by the institutions together to determine the goals to be achieved